Satellite-based approach for seasonal rice area and start of season monitoring - Mathieu, Renaud; Murugesan, Deiveegan; Maunahan, Aileen; Quicho, Emma; Sataphaty, Sushree; Dossou-Yovo, Elliott Ronald; Salif, Doumba; Akpoffo, Marius; Gatti, Luca (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Accurate and regularly updated information regarding the cultivated area of rice, along with forecasts and harvested yields, is indispensable for governments in making informed decisions related to food security, natural resource management, agricultural productivity, and insurance. The RIICE technology approach, tailored for Mali's rice-based systems, has demonstrated its capability to intricately map rice areas and accurately determine the start of growing seasons. The technology adequately captured rice cultivation in irrigated lowlands, rainfed lowlands, and rainfed uplands, although the precision was higher in irrigated and rainfed lowlands compared to rainfed uplands. In the wet season of 2023, the total rice area in Sikasso was estimated to be 335,345 ha, while in the Niger Office, it was 167,736 ha. During the dry season in the Niger Office, the total rice area was estimated to be 49,638 ha. On average, the wet season commences in July in the Niger Delta and in June – July in Sikasso. The RIICE tool provides an efficient alternative to conventional terrestrial methods that are not only time-consuming and expensive but also often subject to inquiries regarding the accuracy of area and start-of-growing-season statistics.